The trouble with Sauling around : conversion in ethnic American autobiography, 1965-2002 - Walker, Madeline Ruth, 1958- (University of Iowa Press, 2011)
℗¡Examining autobiographical texts by Malcolm X (The Autobiography of Malcolm X), Oscar Zeta Acosta (The Autobiography of a Brown Buffalo and Revolt of the Cockroach People), Amiri Baraka (The Autobiography of LeRoi Jones), and Richard Rodriguez ℗¡(Hunger of Memory, Days of Obligation, and Brown), Walker questions the often rosy views and simplistic binary conceptions of religious conversion. Her reading of these texts takes into account the conflict and serial changes the authors experience in a society that marginalizes them, the manner in which religious conversion offers ethnic Americans & ld.